2020
DOI: 10.4236/ape.2020.103017
|View full text |Cite
|
Sign up to set email alerts
|

Can the Core Stability Training Influences Sprint and Jump Performances in Young Basketball Players?

Abstract: The core is the center of the functional kinetic chain providing the proximal stability for the distal mobility and function of the limbs. The study aims to verify the effects of an integrative core stability training on jump and sprint performance in young basketball players. Young basketball players were involved in the study (n = 42, 16 female, 26 male) whose age, stature and weight were respectively (average ± ds) 8.22 ± 0.4 years, 118.2 ± 3.7 cm and 28.8 ± 4.9 kg and was randomly divided in Training Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…(4) Core muscle training: the training was from the easier to the more advanced according to the situation. e exercises included single bridge exercise, double bridge exercise, exercise for hip and knee flexion with Bobath ball under both lower limbs, unilateral exercise of the affected lower limb, and exercise for hip and knee extension [12][13][14], which asked the patient to be in a supine position. e training lasted for 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…(4) Core muscle training: the training was from the easier to the more advanced according to the situation. e exercises included single bridge exercise, double bridge exercise, exercise for hip and knee flexion with Bobath ball under both lower limbs, unilateral exercise of the affected lower limb, and exercise for hip and knee extension [12][13][14], which asked the patient to be in a supine position. e training lasted for 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…One study (17%) evaluated the effect of neuromuscular training on selected parameters of functional movement (Vitale et al, 2018). Regarding the sport, eleven studies (85%) were conducted in team sports, such as baseball, basketball, cricket, football, handball, soccer, and touch ball (Stanton et al, 2004;Nesser et al, 2008;Nesser and Lee, 2009;Chaudhari et al, 2011;Saeterbakken et al, 2011;Ozmen, 2016;Anand et al, 2017;Sannicandro and Cofano, 2017;Kuhn et al, 2019;Felion and DeBeliso, 2020;de Bruin et al, 2021) and two studies (15%) were carried out in individual sports, such as cycling and skiing (Abt et al, 2007;Vitale et al, 2018).…”
Section: The Role Of Neuromuscular Control Of Core Stability In Funct...mentioning
confidence: 99%
“…The analysis of the literature in this scoping review related to the role of core stability in functional movement and/or athlete performance revealed that nine studies (69%) were conducted with regularly competing high school or university athletes or athletes from lower competitions (Stanton et al, 2004;Abt et al, 2007;Chaudhari et al, 2011;Saeterbakken et al, 2011;Ozmen, 2016;Anand et al, 2017;Kuhn et al, 2019;Felion and DeBeliso, 2020;de Bruin et al, 2021), three studies (23%) with young elite athletes (Nesser et al, 2008;Nesser and Lee, 2009;Vitale et al, 2018), and one study (8%) with very young athletes (Sannicandro and Cofano, 2017).…”
Section: Gaps and Limitations Revealed In The Literature Suggestions ...mentioning
confidence: 99%
“…Yet, this factor should be revisited in the future, as the factors "positional strength" and "core strength" gained importance in basketball talent evaluation over the past few year, with some research behind it providing a promising foundation (e.g. Tsukagoshi et al, 2011;Sannicandro and Cofano, 2017).…”
Section: Sport-specific Physical Capabilitiesmentioning
confidence: 99%